Extremism, Campaigning and Ambiguity - Andreas Westermark (Uppsala University, Department of Economics, 1999)
This paper studies a model of how political parties use resources for campaigning to inform voters. We show existence of equilibrium under mild assumptions for an arbitrary number of parties. The main result is that if the parties are more extreme, then they spend less resources on campaigning (on average), compared with moderate parties. The reason is the following. Consider voters that are informed by one party only, say party 1. If both parties move closer to each other, then the actual and expected platform moves closer to the indifferent voters peak. By concavity of preferences, the increase in payoff of voting for the party that informed is bigger than the increase in payoff of voting for the other party. Thus, the previously indifferent voter now strictly prefers party 1. The effect makes parties gain more votes by informing when parties are moderate. Since spending increases, voters are (on average) more informed when parties are moderates.
urn:nbn:se:uu:diva-2448
Keywords: C72; D72; D89; 330; Political Parties; Campaigning; Politische Partei; Wahlverhalten; Öffentlichkeitsarbeit; Theorie